The Scramble for Religion and Secularism in Pre-Colonial Africa - Igboin, Benson Ohihon (Religions, 2022)
The debate on the existence of religion in Africa is far from over; it reverberates in new dimensions but asking the same old questions in newer ways. The same argument is being extended to secularism. This article takes a critical look at the concepts, religion and secularism in sub-Saharan pre-colonial Africa, raising the recurring question still maintained by the West whether there was ‘religion’ in Africa at the turn of colonialism. It argues that where no religion exists, the notion of secularism as understood by the West, cannot also exist since the latter is not just the ‘opposite’ of the former, but in actual fact, streams from it. However, since the position of ‘non-religion’ in Africa could not be sustained by the West, the question of how and why ‘secularism’ was not also ‘discovered’ in pre-colonial Africa spontaneously arises. Not denying the widespread diversities of religious beliefs in pre-colonial Africa, this paper argues for the existence of religion, and presence and praxis of religio-secularity, which is non-atheistic in nature that also foregrounds the practice of ‘secularity’ in post-colonial Africa.